2007
DOI: 10.1002/jts.20247
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depressive, and posttraumatic stress symptoms in mothers of children with type 1 diabetes

Abstract: This study investigated the prevalence of mothers' anxiety, depression, and posttraumatic stress disorder (PTSD) symptoms triggered by their child's type 1 diabetes and identified individual diabetes-related traumatic stressors. Sixty mothers of children who had been diagnosed with diabetes within the past 5 years were interviewed using the Structured Clinical Interview (SCID) DSM-IV-PTSD module, and completed the Posttraumatic Stress Diagnostic Scale (PDS) and the Hospital Anxiety and Depression Scale (HADS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 40 publications
4
65
2
2
Order By: Relevance
“…Moreover, contrary to other studies, such as the study of Horsch et al (2007) that included parents of young children (1-16 years), our sample included parents of children aged 8 to 18…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, contrary to other studies, such as the study of Horsch et al (2007) that included parents of young children (1-16 years), our sample included parents of children aged 8 to 18…”
Section: Discussionmentioning
confidence: 99%
“…Reporting on the same sample, Horsch et al (2007) found 10% of mothers to meet criteria for the diagnosis of PTSD, and a further 15% to meet criteria for the partial diagnosis (i.e., two out of three symptom clusters present) . The mean total score (frequency) for the PDS was 8.20…”
Section: Resultsmentioning
confidence: 96%
“…(SD = 8.90) (see Horsch et al, 2007 for more details). The mean score for the FRQ was 15.71 (SD = 8.39).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These symptoms can include hypervigilance, resulting in an over-monitoring of their child's disease management or conversely, avoidance resulting in under-monitoring. Research has demonstrated that 10% of mothers of children who had diabetes met criteria for a diagnosis of PTSD, while another 15% of mothers displayed some of the symptoms, partially meeting the criteria for this diagnosis (Horsch et al, 2007). Symptoms related to parental experiences of "PTSD" may increase, when the child has mental health problems in addition to his or her diabetes.…”
Section: Parental Adjustmentmentioning
confidence: 99%